Contrast-enhanced ultrasound (CEUS) of cystic renal lesions in comparison to CT and MRI in a multicenter setting - Lerchbaumer, Markus Herbert; Putz, Franz Josef; Ruebenthaler, Johannes; Rogasch, Julian; Jung, Ernst-Michael; Clevert, Dirk-Andre; Hamm, Bernd; Makowski, Marcus; Fischer, Thomas (Clinical Hemorheology and Microcirculation, 2020)
PURPOSE: Contrast-enhanced-ultrasound (CEUS) has been frequently used in assessment of cystic renal lesions. OBJECTIVE: The aim of this study was to investigate the Bosniak classification in CEUS compared to CT and MRI in a multi-center setting. METHODS: Bosniak classification in CEUS examinations of cystic renal lesions were compared to imaging findings in computed-tomography (ceCT) and magnetic-resonance-imaging (ceMRI). Imaging results were correlated to histopathological reports. All examinations were performed by experts (EFSUMB level 3) using up-to-date CEUS examination-protocols. RESULTS: Overall, 173 cystic renal lesions were compared to subgroups CT (n = 87) and MRI (n = 86). Using Bosniak-classification 64/87 renal cysts (73.6%) were rated equal compared to CT with upgrade of four lesions (4.6%) and downgrade of 19 lesions (21.8%) by CT (Intra-class-correlation [ICC] coefficient of 0.824 [p < 0.001]). CEUS compared to MRI, presenting different scoring especially in classes Bosniak IIF (n = 16/31) and Bosniak III (n = 16/28) with an ICC coefficient of 0.651 (p < 0.001). CONCLUSION: CEUS can visualize even finest septal and small nodular wall enhancement, which may result in an upgrade of cystic lesions into a higher Bosniak class compared to CT or MRI. Thus, a modification of the Bosniak classification on CEUS may reduce unnecessary biopsies and surgery.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Bosniak; CEUS; Contrast-enhanced ultrasound; renal cyst